Representation matters : national identity, marginalisation and intersectionality in permanent exhibition curation and museum strategy of the National Museum of Finland - Lehmuskallio, Lilja (Taideyliopiston Sibelius-Akatemia, 2021)
The network of meanings and values a national museum contains and upholds is vast and complex. As a collective memory of the society, a contemporary national museum institution needs to examine the power structures which shape its curatorial and institutional choices. As the authority of the past, present and future representations of Finnish national identity the National Museum of Finland holds a great responsibility in terms of inclusion and representation of all. The thesis is focused on how the National Museum of Finland is constructing national identity in their current permanent exhibitions and why there is a lack of more diverse representation considering minority and marginalised groups and identities in the Finnish national narrative and identity. The study aims to show the necessity of re-examining historical knowledges and truths, and the necessity to diversify the representations of identities constructing the national identity through an intersectional approach, in consideration of the diversity of people living in Finland in terms of race/ethnicity, socio-economic status/class, ability, gender and sexuality. This multidisciplinary study operates in the fields of arts management, feminist museology and critical heritage studies. The results suggest that the core issue in increasing minority representations is in the curatorial definition of the exhibition's core concept to what the visitor should identify themselves with (samastumisen kohde). In order to create social cohesion through an inclusive conception of Finnish national identity, intersectional approach is needed in re-defining the core concept of identifying.
Keywords: museot; kulttuuriperintö; kansallinen identiteetti; Suomi; museologia; näyttelyt; identiteetti; sukupuoli; näyttelytoiminta; taidehallinto; fi=taidehallinto|sv=Arts Management|en=Arts Management|